Analisis Pengendalian Persedaa Kayu dengan Metode Economic Order Quantity (EOQ) di PT. Sumber Tata Citra Mandiri (STCM) - Mega Nurhalizah; Helma Helma (Journal of Mathematics UNP, 2022)
Inventory control of raw materials is one of the primary factors that should be conveyed out by a company. The main goal of a company is to get a high profit by minimizing the cost of the production process. PT. Sumber Tata Citra Mandiri is a manufacturing company that produces plywood. To find out the optimal wood inventory control at PT. Sumber Tata Citra Mandiri, one of the methods used is Economic Order Quantity (EOQ). In view of  results of the study, it was found that the optimal supply of wood in 2021 is 3401.34 m3 with a request recurrence of multiple times in a single year, safety stock is 476.80 m3, and the company makes reorder points at an inventory level of 1319.93 m3 and total the cost of wood supplies according to company policy is Rp. 789.593.600 while the EOQ method is Rp. 544.214.614 so that a savings of Rp. 245.378.986 of the cost of wood supplies according to PT. Sumber Tata Citra Mandiri and companies can consider using the EOQ method in controlling their raw material inventory.